Influência do reuso de águas residuárias na qualidade microbiológica do girassol destinada à alimentação animal - Carvalho, Roseanne Santos de (2013)
The use of treated wastewater for agricultural purposes can become an alternative to maintaining the quality of water bodies, the biota of natural systems as well as relieving demand and preserve the supply of water to use more restrictive. Coupled with the benefits mentioned, reuse positively affects agricultural productivity and significant savings in chemical fertilizers, however, even though there are several advantages inherent in the use of recycled water in agriculture should be to list the fact of the presence of pathogens and organic contaminants. Therefore, this thesis aimed to evaluate the effects of wastewater reuse in the microbiological quality of sunflower (Helianthus annuus L.). The experiment was conducted in the greenhouse of the Department of Agricultural Engineering (DEA), located at the Federal University of Sergipe, São Cristóvão in the period July to September 2012. The treated wastewater were collected in Sewage Treatment Plant (WWTP) Rosa Elze, located in the municipality of São Cristóvão/SE. Irrigation was performed using the following treatments: T1 (100% drinking water Sanitation Company of Sergipe - DESO), T2 (100% of treated wastewater), T3 (50% water DESO + 50% water treated wastewater), T4 (DESO 25% water + 75% of treated wastewater) and T5 (DESO 75% water + 25% of treated wastewater). The irrigation was obtained using the method of FAO 56. We used a completely randomized design (CRD) with five treatments and four replications per plot useful. The data were analyzed according to the parameters recommended by Resolution no. 12 02/01/2001 National Agency of Sanitary Surveillance - ANVISA. We evaluated the parameters of climate, irrigation and water, but the object of the study refers to the microbiological quality of the tops, was carried out the enumeration of coliforms, E. coli, yeasts and Salmonella. The results of the analysis show that the microbiological quality shoots of sunflower is within the standards established by law, however it is necessary to further study the issue, especially in relation to the ground.